Metabolomics data analysis in the context of metabolic networks - Jourdan, Fabien (Henry Stewart Talks, 2018)
Metabolic networks, Reconstructing metabolic networks, Mapping metabolites in genome-scale networks, The challenge of identifiers, Structure and algorithms of metabolic networks, Using biomarkers in biochemical networks, Building subnetworks based on metabolic profiles